Zooplankton community structure in a deep reservoir: seasonal trends and structuring variables? - Geraldes, Ana Maria (2018)
This research aimed at monitoring and characterizing the zooplankton community of Aguieira reservoir (40.33 N; 8.19 W). Aguieira trophic state, nutrient concentration (the highest amounts were observed in summer) and ultimately water quality can be explained by the internal disturbance induced by the intense water level fluctuations. This indeed leads to an increase in suspended particulate material in the water column. Besides, the exposure of littoral sediments to cycles of drying and wetting also increases nutrient availability, preventing macrophytes establishment. These phenomena with the input of allochthonous nutrients originated from human activities in the catchment area lead to the increase of phytoplankton biomass (mainly Cyanobacteria) during summer. When Cyanobacteria were dominating the phytoplankton assemblage, zooplankton community was clearly dominated by the rotifer, Keratella cochlearis and by the caldoceran, Chydorus sphaericus. In the absence of Cyanobacteria, Copidodiaptomus numidicus and Daphnia longispina subsisted as the most representative species. Canonical correspondence analysis (CCA) identified two main environmental gradients that shape zooplankton community: one being temporal mainly related to temperature, and the other, a trophic gradient associated to chlorophyll a concentration, water transparency, nitrates and nitrites. Variance partitioning using CCA revealed that the largest portion (45%) of the total variation explained (70%) was attributed to the interaction between lake and environmental variables.